Histories from the Eternal Love Television Archive (Liberia), 1980–1991 - Mark-Thiesen, Cassandra (African History between Ghana and Switzerland : Essays Honouring Paul Jenkins, 2024)
This collection of essays documents the formative decades of African history across two countries by following the career of a British historian-cum-archivist Paul Jenkins (born 1938 in Sutherland) from West Africa to Central Europe. It retraces his academic path from Ghana to Switzerland while engaging his curiosities in, contributions to, and impact on the development of African history since the 1960s. The volume reflects on Paul’s academic services throughout the 1960s and 1970s, mainly at the University of Ghana (1965–1972) and subsequently at the Basel Mission Archive and University of Basel (1972–2003) in Switzerland – as key sites where he established himself as a teacher and promoter of African history. These episodes led to lasting bonds of intellectual friendships between Paul and an array of inter-/national and -generational scholars of Africa, several of whom are contributing to this volume. Significantly too, the volume highlights the importance of resources Paul curated during the early 1970s, notably his “Abstracts of the Basel Mission’s Gold Coast Correspondences”, through which he increased access to the rich collections of the Basel Mission Archive for scholars of Africa. Altogether, the essays celebrate, engage, interrogate, and push beyond Paul’s numerous past publications and ongoing academic work.